Identifikasi Tipe Penyakit Anemia dengan Menggunakan Metode Random Forest - Farida, Laili Nur (Program Studi Teknik Informatika, 2025)
Anemia is a blood disorder caused by a lack of red blood cells and hemoglobin levels. Based on a survey conducted by the World Health Organization (WHO), anemia affects 1.62 billion people worldwide. As many as 93% of chronic disease patients experience anemia. Anemia can be diagnosed using Complete Blood Count (CBC) which aims to evaluate the total number and characteristics of cell components in the blood. The purpose of this study was to perform Random Forest (RF) classification of anemia. This study used numerical data in the form of blood cell characteristics, consisting of 269 Normocytic Normochromic Anemia patients, 189 Iron Deficiency Anemia patients, and 336 Healthy patients. In this study, the classification process used RF which was then evaluated using the Confusion Matrix, so that the classification evaluation results were obtained in the form of accuracy, sensitivity, and specificity. This study obtained the best results at k of 5 with parameters n estimators, max depth, and min samples leaf of 10, 90, and 4, respectively. The accuracy, sensitivity, and specificity values ​​produced were each 100%.